Pengaruh Kinerja Keuangan dan Tata Kelola Perusahaan Terhadap Nilai Perusahaan pada Industri Telekomunikasi di Bursa Efek Indonesia - Monica Paramita Ratna Putri Dewanti; Hamfri Djajadikerta (Jurnal Akuntansi, 2018)
Investor as a principal want to maximize whealth and prosperity by increasing firm value. Firm value for companies listed as issuer in Indonesia Stock Exchange can be reflected through share price. Firm value can be affected by several factors, such as financial performance and corporate governance. This research aimed to examine the influence of financial performance and corporate governance to firm value in sub-sector telecomunication industry which listed in Indonesia Stock Exchange during 2011 to 2016. The dependent variable is firm value. Meanwhile the independent variables are (1) financial performance which measured by current ratio, receivable turnover, debt to equity ratio, return on assets, and earnings per share and (2) corporate governance which measured by percentage of institutional ownership, percentage of independent board of commissioners, and presence of the audit committee. The result showed that current ratio, receivable turnover, debt to equity ratio, earning per share, and presence of the audit committee partially had no significant influence to firm value. Meanwhile return on assets, percentage of institutional ownership, and percentage of independent board of commissioners partially had significant influence to firm value. Simultaneously current ratio, receivable turnover, debt to equity ratio, return on assets, earnings per share, percentage of institutional ownership, percentage of independent board of commissioners, and presence of the audit committee had significant influence to fim value.Â Keywords:Financial Performance, Corporate Governance, and Firm Value